2016
DOI: 10.1089/cyber.2016.0355
|View full text |Cite
|
Sign up to set email alerts
|

Following Your “Friend”: Social Media and the Strength of Adolescents' Parasocial Relationships with Media Personae

Abstract: Social media have permeated the lives of adolescents and may be altering the way that teens engage with their favorite media celebrities and characters. This study surveyed 316 adolescents to examine the relationship between social media surveillance and the strength of adolescents' parasocial relationships (PSRs) with media personae they follow on social media. Results indicated a significant positive relationship between exposure to media personae on Twitter and strength of PSRs. Adolescents who had experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(65 citation statements)
references
References 13 publications
1
62
0
2
Order By: Relevance
“…Further, Lou and Yuan (2019) defined a social media influencer as “first and foremost a content generator” (p. 59) who attracts substantial number of followers by producing valuable content and profits from promoting sponsored content to his/her followers. Recent research suggests that social media influencers can exert greater influence over adolescents than peers and family members do (Al-Harbi and Al-Harbi, 2017), and that adolescents’ exposure to their favorite media personae on Twitter and interactions with them positively contributed to the strength of their PSR with the media personae (Bond, 2016). During the process of followers’ forming relationship with influencers, influencers’ traits, characteristics of influencer-generated content, as well as the influence of adolescents’ parents, are expected to play indispensable roles (e.g., Schooler et al, 2006; Collier et al, 2016; Lou and Yuan, 2019).…”
Section: Adolescents and Social Media Influencersmentioning
confidence: 99%
“…Further, Lou and Yuan (2019) defined a social media influencer as “first and foremost a content generator” (p. 59) who attracts substantial number of followers by producing valuable content and profits from promoting sponsored content to his/her followers. Recent research suggests that social media influencers can exert greater influence over adolescents than peers and family members do (Al-Harbi and Al-Harbi, 2017), and that adolescents’ exposure to their favorite media personae on Twitter and interactions with them positively contributed to the strength of their PSR with the media personae (Bond, 2016). During the process of followers’ forming relationship with influencers, influencers’ traits, characteristics of influencer-generated content, as well as the influence of adolescents’ parents, are expected to play indispensable roles (e.g., Schooler et al, 2006; Collier et al, 2016; Lou and Yuan, 2019).…”
Section: Adolescents and Social Media Influencersmentioning
confidence: 99%
“…Some studies have indicated that a fan's social media use with celebrities tend to lead to higher parasocial bonds with the celebrity (i.e. Bond, 2016;Chung & Cho, 2014). Previous research has also attempted to examine the relationship between celebrity characteristics, such as attitude and background homophily (Schroath, 2016), social attraction (i.e.…”
Section: Parasocial Interaction and Social Mediamentioning
confidence: 99%
“…There are some phenomena unique to SM connectedness such as parasocial relationship (PSR) development. A PSR defines the oneway relationship between a person and a media persona, mediated through television, radio, cartoon, or SM [12]. Needs for social interaction and attachment might lead to PSRs.…”
Section: Introductionmentioning
confidence: 99%